Drug Discovery for Overcoming Chronic Kidney Disease (CKD): Development of Drugs on Endothelial Cell Protection for Overcoming CKD - Keisuke Ishizawa; Kunihisa Yamaguchi; Yuya Horinouchi; Yayoi Fukuhara; Soichiro Tajima; Shuichi Hamano; Shuhei Tomita; Koichiro Tsuchiya; Toshiaki Tamaki (Elsevier, 2009)
Chronic kidney disease (CKD) is becoming a major public health problem worldwide. It is important to protect endothelial function in CKD treatment because injury of the endothelium is a critical event for the generation and progression of CKD. Recently, clinical studies showed that nifedipine, an antihypertensive drug, acts as a protective agent of endothelial cells (ECs). Nifedipine is reported to partially decompose to a nitrosonifedipine that has high reactivity against lipid-derived radicals in vitro. However, it is still unclear whether nitrosonifedipine is a biologically active agent against endothelial injury. We observed that nitrosonifedipine was converted to radical form by reaction with cultured ECs. The cumene hydroperoxide mediated cytotoxity was reduced by nitrosonifedipine in cultured human glomerular ECs (HGECs). Also nitrosonifedipine suppressed the expression of TNF-α-induced intercellular cell adhesion molecule-1 in HGECs. Chronic administration of Nω-nitro-L-arginine methyl ester (L-NAME) caused systemic arterial hypertension, endotherial injury, and renal dysfunction. In L-NAME- induced hypertensive rats, nitrosonifedipine treatment improved not only the acetylcholine-induced vasodilation of the aortic rings, but also renal dysfunction such as increasing the levels of serum creatinine and urinary protein excretion. Our preliminary data suggest that nitrosonifedipine is a new and useful drug for the treatment of CKD involving ameliorating effects on EC disorder. Keywords:: chronic kidney disease (CKD), endothelial dysfunction, nitrosonifedipine, antioxidative effect